Predator-avoidance of larval black-bellied salamanders (Desmognathus quadramaculatus) in response to cues from native and nonnative salmonids. Issue 6 (2nd November 2022) - Dempsey, Brian L.; Roden, John W.; Bidwell, Joseph R.
Abstract : Fish are significant predators of amphibian larvae in streams and larvae can detect these predators through both visual and olfactory cues. The ability to effectively recognize these cues may depend on the evolutionary history of predator and prey such that recently introduced predators may not be recognized as readily as those that have consistently coexisted with the prey species. As such, the relatively recent introduction of rainbow trout ( Oncorhynchus mykiss ) into Southern Appalachian headwater streams where the black-bellied salamander ( Desmognathus quadramaculatus) and brook trout ( Salvelinus fontinalis ) naturally coexist has raised concern. The objective of this study was to determine whether black-bellied salamander larvae respond to cues from introduced rainbow trout. To evaluate this, salamander activity metrics (general activity and number of movements) were recorded before and after exposure to either native trout predator cue (brook), introduced trout predator cue (rainbow), or conditioned tap water (control). Larvae were collected from different stream reaches based on their cooccurrence with brook trout only, rainbow trout only, rainbow and brook trout, or no trout predators. Larvae that co-occur with trout reduced their activity when exposed to brook trout predator cue, but their response to rainbow trout predator cue depended on their previous co-occurrence. A follow-up test to determine the influence of alarm cue on predator response indicated that the alarm cue enhanced the response to the rainbow trout predator.